Evaluation of Person-Centredness in Rehabilitation for People Living with Dementia Is Needed: A Review of the Literature - Kate Allen Christensen; Karen-Margrethe Lund; Jette Thuesen (Journal of Aging Research)
Background. With an expected increase in the prevalence of dementia, change in care policies and healthcare systems worldwide is needed. Rehabilitation is increasingly recognised as contributing to dementia care. Rehabilitation subscribes to person-centredness, and thus, evaluations of person-centredness in rehabilitation for people living with dementia are relevant in order for healthcare professionals to know how best to practice person-centredness. Aim. The aim of this study was to identify methods of evaluating person-centeredness in rehabilitation for people living with dementia. Materials and Methods. Review of the literature using the search terms dementia, person-centredness, and rehabilitation or occupational therapy. Databases searched included: CINAHL, PubMed, Embase, PsycINFO, OTseeker, and SveMed+. The study included peer-reviewed articles from year 2000 to 2018 in Danish, English, Norwegian, or Swedish. Results. Only one academic article met the inclusion criteria. In that article, person-centred practice was evaluated using observation and interview as well as analytical frameworks from person-centred care and occupational therapy. Conclusion. Evaluations of person-centred practice in rehabilitation for people living with dementia in peer-reviewed literature are lacking. Evaluations are needed to identify effective strategies to pursue and uphold person-centred care. Given the dearth of research on evaluations of person-centredness in rehabilitation, this article included research in person-centred dementia care in the discussion, which potentially can inspire practice and research of rehabilitation for people living with dementia. To understand the complex nature of person-centredness, a variety of research methodologies of qualitative and quantitative characters are recommended for evaluations.